Understanding the Botnet Phenomenon - Dr. Priyanka Surendran (International Journal of Engineering and Management Research, 2018)
Internet threats have increased manifold with the arrival of botnets. Many organizations worldwide and the social networks have been affected by botnets. Numerous researches have been carried to understand the concept of bots, C&C channels, botnet and botmasters. These botnets have been able to update itself regularly which makes them very difficult to be detected. The purpose of this paper is to understand the of behavior of botnets and its affect on the virtual world. The paper has also analyzed the types of botnets, lifecycle and elements of botnets.